Estética marxista e mediação através da arte: perspectivas do cotidiano profissional do assistente social - Leão, Ricardo de Holanda (2022)
This thesis is presented in the professional category of social services to start an important debate about the mediation of art in the daily life of the profession. We consider the Marxist perspective in the composition of the social environment, which is used to relate the theme of the mediation of art on the daily scenarios of the social worker. This perspective intends to address the aspect of the social being inside the capitalist system, the cultural issues of this profession on its praxis, as well as the professional relations among the contradictions of capitalism. Our research object is the professional performance of the social worker who uses art as mediation, working on it beyond the instrumental, as instrumentality. The Marxist approach is included in the understanding of the critical debate as a path to comprehend the transformation of reality, and such a transformation is connected with the movement of society. Art is placed as an important means of development of the social being in history, used to develop the criticism and the creativity of the human being. Art also broadens the notion of rights and social awareness, and it is essential for the strengthening of the professional project of the Social Service. In this way, we aim to understand how knowledge of the Marxist perspective can contribute to the professional daily life of the social worker who uses art in mediation with the society. To do so, we approached the debate on daily life (NETTO & CARVALHO, 2000; HELLER, 2000; LUKÁCS, 1966; LEFEBVRE, 1991), the Marxist perspective, and the place of art in society (FREDERICO, 2013; VASQUEZ, 2010). We also made use of studies about being social in contemporary times (LUKÁCS, 2010, 2012; MARX, 2004, 2014), as well as the approaches about consciousness (LUKÁCS, 2010, 2018), experience (THOMPSON, 1981), among others references. In addition we bring the debate on the "social issue" and social services (SANTOS, 2012; YASBEK, 1999), the matter of mediation (PONTES, 1995), beyond aspects about professional performance (MARTINELLI, 2008; NETTO, 2008; GUERRA, 2012) working on training and practice, highlighting the technical-operative subjectives. The methodological procedures are based on the theoretical references pointed out, as well as the experiences of social services professionals and users of the social workers policy of the city of São Paulo. We worked using a qualitative approach, through the use of oral history through interviews and meetings. The Palacete dos Artistas was the place of interaction with users, where we were able to collect interesting material for the debate of this thesis. The writing of the thesis is divided into two parts. The first one talks about daily life, society and art in the construction of society and of the professional performance. The second part covers the debate of the category of Social Service before the Marxist and professional perspectives, and also the professional performance of the social workers over such perspectives